Study on the energy-band structure of an InAs/InGaAs/GaAs quantum-dot infrared photodetector structure - Kim, J. S.; Kim, E. K.; Song, J. D.; Choi, W. J.; Lee, J. I. (KOREAN PHYSICAL SOC, 2006)
We studied the energy-band structure of InAs/InGaAs/GaAs quantum-dot infrared photodetector (QDIP) with dot-in-a-well structure by performing deep-level transient spectroscopy (DLTS) and photoluminescence measurements. The confined energy levels of InAs/InGaAs quantum dot and the InGaAs/GaAs quantum well in the dot-in-a-well QDIP structure were analyzed. DLTS revealed activation energies of 352 meV and 125 meV, which originated from the confined levels of the quantum dot and quantum well, respectively. These energy levels were also identified as 290 meV and 150 meV in PL measurements, respectively, based on the PL measurements.
Keywords: GAAS; LAYER